The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14704/nq.2019.17.1.1318
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Transmitted Light Experience during Meditation: A Pilot Hyperscanning Study

Abstract: Certain individuals during deep meditative state can give out an aura or 'light, which is perceived by others through some unknown connections, visual, telepathic or other. Despite various anecdotal, historical accounts of such induced light experience (ILE), its underlying neural mechanisms are not known. In this pilot study, we investigated the neural correlates of ILE by simultaneously recording the EEGs of an expert meditation Teacher, who is claimed to elicit ILE, and his Pupil (N=2) during joint meditati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Setting. A majority of studies (25/28, 89%) were conducted in the lab while 11% (3/28) of the studies were done in a natural setting [23,87,90]. For example, Babiloni et al [87] demonstrated that the EEG methodology is suitable for high-quality EEG data in subjects playing in an ensemble outside of a lab.…”
Section: Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Setting. A majority of studies (25/28, 89%) were conducted in the lab while 11% (3/28) of the studies were done in a natural setting [23,87,90]. For example, Babiloni et al [87] demonstrated that the EEG methodology is suitable for high-quality EEG data in subjects playing in an ensemble outside of a lab.…”
Section: Cognitionmentioning
confidence: 99%
“…For example, Babiloni et al [87] demonstrated that the EEG methodology is suitable for high-quality EEG data in subjects playing in an ensemble outside of a lab. Recently, Fenwick et al [90] was the first study to investigate neural synchrony during meditation.…”
Section: Cognitionmentioning
confidence: 99%
“…The following studies explore machine mediated neural and behavioral synchronization in real and virtual environments (Hachmeister et al, 2014 ; Gumilar et al, 2021 ). Similarly, the effect of cooperation on neural synchrony (Abe et al, 2019 ), meditation and monastic debates (Fenwick et al, 2019 ; van Vugt et al, 2020 ), emotional association in groups (Nummenmaa et al, 2014 ; Goldstein et al, 2018 ; Santamaria et al, 2019 ) are included in this paradigm. These studies do not have a single set of specified roles for the participants similar to the previous paradigm apart from the participants all being part of social groups.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that put no restrictions on the participants regarding movement and used wireless or comparatively lighter data acquisition device was considered naturalistic and comprised 59.3% or 38/64 of the papers (Reiterer et al, 2011 ; Ding et al, 2018 ; Greco et al, 2018 ). Some studies restricted the movement of the participants (Dikker et al, 2017 ; Bevilacqua et al, 2019 ) through instructions, monitored ambient lighting (Fenwick et al, 2019 ), used noise-canceling earphones (Balconi, 2016 ) to limit perceived noise. These were considered semi-naturalistic as they do not replicate real-life social interactions on a full scale.…”
Section: Resultsmentioning
confidence: 99%